Relapse after withdrawal from anti‐TNF therapy for inflammatory bowel disease: an observational study, plus systematic review and meta‐analysis. Issue 8 (19th February 2016) - Kennedy, N. A.; Warner, B.; Johnston, E. L.; Flanders, L.; Hendy, P.; Ding, N. S.; Harris, R.; Fadra, A. S.; Basquill, C.; Lamb, C. A.; Cameron, F. L.; Murray, C. D.; et al.
Summary: Background: Infliximab and adalimumab have established roles in inflammatory bowel disease (IBD) therapy. UK regulators mandate reassessment after 12 months' anti‐TNF therapy for IBD, with consideration of treatment withdrawal. There is a need for more data to establish the relapse rates following treatment cessation. Aim: To establish outcomes following anti‐TNF withdrawal for sustained remission using new data from a large UK cohort, and assimilation of all available literature for systematic review and meta‐analysis. Methods: A retrospective observational study was performed on 166 patients with IBD (146 with Crohn's disease (CD) and 20 with ulcerative colitis [UC) and IBD unclassified (IBDU)] withdrawn from anti‐TNF for sustained remission. Meta‐analysis was undertaken of all published studies incorporating 11 further cohorts totalling 746 patients (624 CD, 122 UC). Results: Relapse rates in the UK cohort were 36% by 1 year and 56% by 2 years for CD, and 42% by 1 year and 47% by 2 years for UC/IBDU. Increased relapse risk in CD was associated with age at diagnosis [hazard ratio (HR) 2.78 for age <22 years], white cell count (HR 3.22 for >5.25 × 10 9 /L) and faecal calprotectin (HR 2.95 for >50 μg/g) at drug withdrawal. Neither continued immunomodulators nor endoscopic remission were predictors. In the meta‐analysis, estimated 1‐year relapse rates were 39% and 35% for CD and UC/IBDU respectively. Retreatment with anti‐TNF was successful in 88% for CD and 76% UC/IBDU. Conclusions: Assimilation of all available data reveals remarkable homogeneity. Approximately one‐third of patients with IBD flare within 12 months of withdrawal of anti‐TNF therapy for sustained remission.